Faktor-Faktor Yang Mempengaruhi Kecenderungan Kecurangan Akuntansi Pada LPD Di Kecamatan Seririt - Luh Putu Rida Cinthyani; Ni Luh Gede Erni Sullindawati (Universitas Pendidikan Ganesha, 2020)
The purpose in this study was to determine information asymmetry, spiritual intelligence, obedience to accounting rules, integrity of the prajuru and their influence on accounting fraud in the LPD in Seririt sub-district. This research was conducted in LPD throughout Seririt district. The independent variables of this research are information asymmetry, spiritual intelligence, obedience to accounting rules, integrity of the prajuru and the dependent variable of this study is the tendency of accounting fraud.Quantitative research is a type of research. Primary data is data used in the form of questionnaires distributed to respondents. The population is LPD in the seririt sub-district which amounted to a total sample of 14 LPD using a purposive sample so as to get 48 respondents. In analyzing data using SPSS 20.0 for windows. Based on the test that has been done to get the results, namely: (1) information asymmetry partially positive and significant effect on the tendency of accounting fraud in the LPD in Seririt district, (2) spiritual intelligence partially negative and significant effect on the tendency of accounting fraud in the LPD in the district Seririt, (3) partial observance of accounting rules has a negative and significant effect on the tendency of accounting fraud in the LPD in Seririt sub-district, (4) the integrity of prajuru partially has a negative and significant effect on the tendency of accounting fraud in the LPD in Seririt district.